The Reality of Higher Education in Kuwait in Light of Artificial Intelligence and Future Prospects from the Perspective of Faculty Members: An Exploratory Study (Damascus University Journal of educational and Psychologyical sciences, 2025)
The study aimed to explore the extent to which artificial intelligence (AI) applications are employed in public and private higher education institutions in Kuwait, focusing on the current situation, challenges, and possible solutions. The study used the descriptive method by adapting a questionnaire from Al-Habib's (2022) study, which was previously applied to a similar sample in higher education institutions in Saudi Arabia. Additionally, six personal interviews were conducted with some directors of these institutions to answer three pre-prepared questions. The study's questionnaire consisted of two main axes: the first related to the current use of AI applications, and the second addressed the challenges and obstacles associated with implementing these applications. A total of 218 faculty members from various public and private higher education institutions in Kuwait participated in the study. The results showed that faculty members in both public and private higher education institutions in Kuwait had a moderate level of agreement regarding the current employment of AI applications in the educational process, meeting expectations at the present time. However, they expressed strong agreement regarding several challenges that hinder the adoption of AI applications, with the most significant being the lack of conviction among faculty members about the importance of using AI in their training and the weak technological and digital skills among them. Overall, the study revealed a high level of awareness among many participants about the necessity of integrating AI applications in education, as it represents an indispensable technology for the future. The sample also strongly highlighted the major obstacles limiting the optimal use of this modern technology. The study provided a vision of the importance of utilizing AI applications in educational contexts, emphasizing that it will be a key differentiator and the most crucial factor in improving education quality in the near future
Keywords: Artificial Intelligence; Higher Education